Akuntabilitas Pengelolaan Limbah Berbasis Nilai Kejujuran - Fajrul Falah Muhammad; Novrida Qudsi Lutfillah; Sugeng Sulistiono (InFestasi, 2022)
This study aims to describe and analyze the practice of accountability for managing waste in waste management in companies that are engaged explicitly in managing waste. Research on environmental accountability and accounting has so far been dominated by explanations of environmental accounting application activities with hospital objects. There is still limited research that considers cultural themes and values that underlie the concept of accountability on objects other than hospitals. This study uses a qualitative method with an interpretive paradigm. The results of the study show that the accountability carried out by waste management companies includes environmental, social, economic, and highest accountability to God by emphasizing the value of honesty. The implication of the value of honesty is considered a tool for self-control to raise awareness of maintaining a relationship with God, humans, and the environment. Thus, the value of honesty is an expression of the balance underlying the accountability of waste management. Penelitian ini bertujuan mendeskripsikan dan menganalisis praktik akuntabilitas pengelolaan limbah pengelolaan limbah pada perusahaan yang bergerak khusus mengelola limbah. Penelitian mengenai akuntabilitas lingkungan dan akuntansi lingkungan selama ini didominasi dengan penjelasan aktivitas penerapan akuntansi lingkungan dengan obyek rumah sakit, masih terbatas penelitian yang mempertimbangkan tema budaya dan nilai yang mendasari konsep akuntabilitas pada obyek selain rumah sakit. Penelitian ini menggunakan metode kualitatif dengan paradigma interpretif. Hasil penelitian menunjukkan akuntabilitas yang dilakukan perusahaan pengelolaan limbah mencakup lingkungan, sosial, ekonomi, dan pertanggungjawaban tertinggi kepada tuhan dengan menekankan pada nilai kejujuran. Implikasi nilai kejujuran dinilai sebagai alat untuk pengendalian diri untuk membangkitkan kesadaran menjaga hubungan dengan Tuhan, manusia, dan lingkungan. Dengan demikian, nilai kejujuran merupakan ungkapan dari keseimbangan melandasi akuntabilitas pengelolaan limbah.